Advances in real‐time phase‐contrast flow MRI using asymmetric radial gradient echoes. Issue 5 (22nd June 2015) - Untenberger, Markus; Tan, Zhengguo; Voit, Dirk; Joseph, Arun A.; Roeloffs, Volkert; Merboldt, K. Dietmar; Schätz, Sebastian; Frahm, Jens
Abstract : Purpose: To provide multidimensional velocity compensation for real‐time phase‐contrast flow MRI. Methods: The proposed method introduces asymmetric gradient echoes for highly undersampled radial FLASH MRI with phase‐sensitive image reconstruction by regularized nonlinear inversion (NLINV). Using an adapted gradient delay correction the resulting image quality was analyzed by simulations and experimentally validated at 3 Tesla. For real‐time flow MRI the reduced gradient‐echo timing allowed for the incorporation of velocity‐compensating waveforms for all imaging gradients at even shorter repetition times. Results: The results reveal a usable degree of 20% asymmetry. Real‐time flow MRI with full velocity compensation eliminated signal void in a flow phantom, confirmed flow parameters in healthy subjects and demonstrated signal recovery and phase conservation in a patient with aortic valve insufficiency and stenosis. Exemplary protocols at 1.4–1.5 mm resolution and 6 mm slice thickness achieved total acquisition times of 33.3–35.7 ms for two images (7 spokes each) with and without flow‐encoding gradient. Conclusion: Asymmetric gradient echoes were successfully implemented for highly undersampled radial trajectories. The resulting temporal gain offers full velocity compensation for real‐time phase‐contrast flow MRI which minimizes false‐positive contributions from complex flow and further enhances the temporal resolution compared with acquisitions with symmetric echoes. Magn Reson Med 75:1901–1908, 2016. © 2015 Wiley Periodicals, Inc.